Evaluation of Chemistry and Concentration of Air Pollutants from Brick Factories in Nahrawan Area, Northeast Baghdad, Using GIS Methods - Hashim, Bassim M; Abdulwahed, Esam A; Sultan, Maitham A (Al-Nahrain Journal of Science, 2018)
This study aimed to measure the concentration of the total suspended particle (TSP) and gaseous pollutants (CO, CO2, SO2 and NO2) that emitted from Nahrawan’s brick factories and compare it to its counterparts from the village of Nahrawan. Samples from 17 sites, as well as Nahrawan village were collected in the current study. The results showed that TSP had the highest concentration (9801.7 μg/m3), exceeding world health organization (WHO) standard in all study sites, including Nahrawan village. The results also indicated that CO concentration at most sites exceeded WHO standard. The results showed that CO2 concentration in all the sites exceeded WHO standard (250 ppm), while the measure taken from Nahrawan village registered lower. SO2 was not record in air of Nahrawan village, yet it formed the highest concentration (0.1 ppm) in the study area, much greater than the WHO standard (0.01 ppm). On the other hand, NO2 assumed the highest concentration of (0.3 ppm) again, higher than WHO standard of (0.11 ppm) across all sites, except Nahrawan village. Spatial analysis was performed to generate spatial patterns of air pollutants released by bricks factories in Nahrawan region and to represent the values of wind speed. Visualization of the spatial patterns revealed that the pollutants highly concentrated in the central and southern study area and is located towards the prevailing wind.